Clinical and Molecular-Genetic Insights into the Role of Oxidative Stress in Diabetic Retinopathy: Antioxidant Strategies and Future Avenues - Silvia M. Sanz-González; José J. García-Medina; Vicente Zanón-Moreno; María I. López-Gálvez; David Galarreta-Mira; Lilianne Duarte; Mar Valero-Velló; Ana I. Ramírez; J. Fernando Arévalo; María D. Pinazo-Durán; on behalf of the Valencia Study Group on Diabetic Retinopathy (VSDR) (MDPI AG, 2020)
Reactive oxygen species (ROS) overproduction and ROS-signaling pathways activation attack the eyes. We evaluated the oxidative stress (OS) and the effects of a daily, core nutritional supplement regimen containing antioxidants and omega 3 fatty acids (A/ω3) in type 2 diabetics (T2DM). A case-control study was carried out in 480 participants [287 T2DM patients with (+)/without (−) diabetic retinopathy (DR) and 193 healthy controls (CG)], randomly assigned to a daily pill of A/ω3. Periodic evaluation through 38 months allowed to outline patient characteristics, DR features, and classic/OS blood parameters. Statistics were performed by the SPSS 24.0 program. Diabetics displayed significantly higher circulating pro-oxidants (p = 0.001) and lower antioxidants (p = 0.0001) than the controls. Significantly higher plasma malondialdehyde/thiobarbituric acid reactive substances (MDA/TBARS; p = 0.006) and lower plasma total antioxidant capacity (TAC; p = 0.042) and vitamin C (0.020) was found in T2DM + DR versus T2DM-DR. The differential expression profile of solute carrier family 23 member 2 (SLC23A2) gene was seen in diabetics versus the CG (p = 0.001), and in T2DM + DR versus T2DM − DR (p < 0.05). The A/ω3 regime significantly reduced the pro-oxidants (p < 0.05) and augmented the antioxidants (p < 0.05). This follow-up study supports that a regular A/ω3 supplementation reduces the oxidative load and may serve as a dietary prophylaxis/adjunctive intervention for patients at risk of diabetic blindness.